FEMINISM AND MEDIA REPRESENTATION:A SEARCH FOR EQUITY, FAIRNESS AND EMPOWERMENT (Lead City International Journal of Library, Information & Communication Sciences, 2024)
Mediarepresentation and feminism have long been linked in conversations about empowerment,justice and equity. The goal of feminism is to define and establish the political, economic,personal, and social equality of the gender through a variety of sociopolitical movements andideas. The aim of the study is to situate the interconnectedness of feminism and mediarepresentation and the search for equity, fairness and empowerment. This study adoptedcultivation media theory; with the use of qualitative methodology while secondary data wasutilized. Other academics’ studies as well as press articles served as sources. The conclusion ofthis study is that the exploration of feminism and media representation underscores an ongoingquest for equity, fairness, and empowerment. Across various forms of media, from film andtelevision to advertising and social media, the portrayal of women has evolved over time, yetchallenges persist in achieving true gender parity. The study recommends that promoting equityand fairness within feminism involves advocating for gender equality while recognizing andaddressing intersecting forms of discrimination and privilege. There is need to embrace anintersectional approach to feminism that acknowledges the interconnected nature of socialidentities such as race, class, sexuality, disability, and gender.